FAKTOR-FAKTOR PENENTU TARIF MASUK PENGUNJUNG TAMAN NASIONAL (Studi Kasus Taman Nasional Gunung Merapi) - Setiyawati Titi; Yanto Santosa; Dudung Darusman (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
Almost all Indonesia’s national parks (NP) faced the challenge of managing their finances. One innovative way of raising additional funds was the rate of incoming visitors. Determination of entrance fee for national park was currently based on regional allocation of market system not on conditions and potentials of the respective national parks. Fees for incoming visitors were uniform for all national parks within a single regional allocation market. Such uniformity had resulted in relatively low fees for some NP and relatively high for others. As a price, visitors entrance fee required to be assessed not only from the user side but also from the manager’s, especially in national parks with high potential number of visitors, such as Gunung Merapi (GMNP) with 165,851 visitors annually. The objectives of this study were to (1) identify the factors that affect the amount of entrance fee, (2) determine entrance fee based on GMNP annual management expenses using main cost approach, (3) determine entrance fee based on visitors using travel cost method and (4) determine entrance fee based on annual expenses for GMNP management and visitors. Results of the analysis showed that factors affecting GMNP entrance fee were: (1) based on annual management expenses were operational cost and total number of visitors, (2) based on visitors were travel cost, tourism attractions and total number of visitors per group, and (3) based on annual GMNP management expenses and visitors, were travel cost, tourism attractions, number of visitors per group, operational cost and total number of visitors. Keywords : eexpense, entrance fee, scenario, visitors